2021
DOI: 10.3390/ijms222212414
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of NAC Transcription Factor Family in Juglans mandshurica and Their Expression Analysis during the Fruit Development and Ripening

Abstract: The NAC (NAM, ATAF and CUC) gene family plays a crucial role in the transcriptional regulation of various biological processes and has been identified and characterized in multiple plant species. However, genome-wide identification of this gene family has not been implemented in Juglans mandshurica, and specific functions of these genes in the development of fruits remain unknown. In this study, we performed genome-wide identification and functional analysis of the NAC gene family during fruit development and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 69 publications
3
18
0
Order By: Relevance
“…These results are in constant with preceding reports such as Jin et al (2017) reported that the NAC gene family experienced a divergence rate of 145 mya in dicotyledonous and grass plants, furthermore, Tuskan et al (2006) reported that a whole-genome duplication occurred in Populus at 60–65 mya. Moreover, 12 PeNAC gene pairs were segmental duplicated and 11 gene pairs were tandem duplicated, which are in consistent with Li X. et al (2021) and Li P. et al (2021) reports, who also found the segmental and tandem duplicated genes in genome-wide NAC family analysis. In addition, a comprehensive syntenic analysis of P. edulis NAC with A. thaliana, Z. jujuba , T. cacao , A. hypogaea , and C. sativa NAC identified 284 NAC gene pairs, of which, the maximum 86 NAC gene pairs were between P. edulis and A. hypogaea (38 PeNAC -61 AhNAC ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are in constant with preceding reports such as Jin et al (2017) reported that the NAC gene family experienced a divergence rate of 145 mya in dicotyledonous and grass plants, furthermore, Tuskan et al (2006) reported that a whole-genome duplication occurred in Populus at 60–65 mya. Moreover, 12 PeNAC gene pairs were segmental duplicated and 11 gene pairs were tandem duplicated, which are in consistent with Li X. et al (2021) and Li P. et al (2021) reports, who also found the segmental and tandem duplicated genes in genome-wide NAC family analysis. In addition, a comprehensive syntenic analysis of P. edulis NAC with A. thaliana, Z. jujuba , T. cacao , A. hypogaea , and C. sativa NAC identified 284 NAC gene pairs, of which, the maximum 86 NAC gene pairs were between P. edulis and A. hypogaea (38 PeNAC -61 AhNAC ).…”
Section: Discussionsupporting
confidence: 89%
“… Asefpour Vakilian (2020) reported that the miRNA plays a significant role under plant stresses. In recent years, with the development of bioinformatics, molecular biology techniques and the crucial role of NAC genes, the gnome wide identification of NAC genes has already been reported in numerous plants including 117 NAC genes in Arabidopsis and 151 in rice ( Ooka et al, 2003 ), 87 genes in maize ( Wang G. et al, 2020 ), 145 genes in sorghum ( Sorghum bicolor ) ( Kadier et al, 2017 ), 132 genes in peanut ( Arachis hypogaea ) ( Li P. et al, 2021 ), 113 genes in Medicago sativa ( Min et al, 2020 ), 90 genes in eggplant ( Solanum melongena ) ( Wan et al, 2021 ), 102 genes in apricot ( Prunus sibirica ) ( Xu et al, 2021 ), and cacao ( Theobroma cacao ) ( Shen et al, 2019 ), 167 genes in barley ( Murozuka et al, 2018 ), 64 genes in pitaya ( Hylocereus ) ( Hu et al, 2022 ), 114 genes in walnut ( Juglans mandshurica ) ( Li X. et al, 2021 ), 114 genes in longan ( Dimocarpus longan ) ( Munir et al, 2020 ), 154 genes in tobacco ( Nicotiana tabacum ) ( Li et al, 2018 ), 91 genes in cucumber ( Cucumis sativus ) ( Liu et al, 2018 ), 180 genes in apple ( Malus domestica ) ( Su et al, 2013 ), 147 genes in foxtail millet ( Setaria italica ) ( Puranik et al, 2013 ), 55 genes in jujuba ( Ziziphus jujuba ) ( Li M. et al, 2021 ), 163 genes in poplar ( Populus Trichocarpa ) ( Hu et al, 2010 ), 152 genes in soyabean ( Glycine max ) ( Le et al, 2011 ), and 104 genes in pepper ( Capsicum annuum ) ( Diao et al, 2018 ), respectively. However, the NAC gene family has not been studied in passion fruit.…”
Section: Introductionmentioning
confidence: 99%
“…According to the conserved domain of the A. truncatum WRKY protein, the family can be divided into different groups. The Clustalw algorithm analysis was performed, and the multiple sequence alignment analysis using the default parameters in MEGA6.0: 1000 replicates for bootstrap analysis and pairwise deletion [ 37 , 38 ]. Then, the phylogenetic tree was constructed from the alignment results using neighbor-joining (NJ) method.…”
Section: Methodsmentioning
confidence: 99%
“…is a perennial woody species, with economic and ecological value. The distribution of J. mandshurica is in Japan, North Korea, the Russian Far East, and northeast China [ 31 , 32 ]. In particular, it possesses the characteristics of multipurpose components, long life, and heterodichogamy.…”
Section: Introductionmentioning
confidence: 99%